(untitled) (Scientific journal of the Fergana State University, 2025)
This article is dedicated to studying the importance of sports in the formation of national identity. National identity encompasses the unique characteristics, traditions, and values of each nation, playing a significant role in social life. The use of sports in shaping national identity among students is crucial for their physical, spiritual, and social development. The article presents thoughts on the concept of national identification, the individual’s sense of being part of a national society, and the unifying role of sports activities.